Shufeng Jiedu Capsules for treating wind-heat syndrome respiratory diseases: a systematic review and meta-analysis - Liu, Jia-Min; Wang, Lu; Zhao, Gui-Xiang; Zhang, Hai-Long (Frontiers in Pharmacology, 2025)
BackgroundThis study systematically evaluates the efficacy and safety of Shufeng Jiedu Capsules in treating respiratory diseases with wind-heat syndrome patterns, providing clinical guidance and a reference for developing new “syndrome-dominating disease management” medications.MethodsA systematic search of CNKI, Wanfang, VIP, SinoMed, PubMed, Cochrane Library, Embase, Web of Science, and trial registries identified randomized controlled trials (RCTs) assessing Shufeng Jiedu Capsules for wind-heat syndrome respiratory diseases (from inception to December 2024). Two researchers independently screened studies and extracted data using predefined criteria. Methodological quality was assessed using the Cochrane Risk of Bias tool. RevMan 5.3 and Stata 18 were used for data analysis, and evidence quality was graded using the GRADE system.ResultsTwenty-five RCTs involving 2681 patients were included, with 1339 in the experimental group and 1342 in the control group. The GRADE assessment indicated predominantly low or very low evidence certainty, mainly due to methodological flaws such as unclear allocation concealment, lack of blinding, and absence of protocol registration, which increased the risk of bias. Meta-analysis showed that Shufeng Jiedu Capsule combined with conventional biomedical therapy outperformed biomedical therapy alone. It improved the effective rate of traditional Chinese medicine syndromes (risk ratio [RR] = 1.17, 95% CI 1.10 to 1.24, P < 0.00001) and shortened the resolution time of cough (mean difference [MD] = −0.97, 95% CI −1.09 to −0.85, P < 0.00001) and phlegm (MD = −0.48, 95% CI −0.96 to −0.17, P = 0.002). These outcomes were supported by high-quality GRADE evidence. Moderate-quality evidence supported improvements in imaging absorption rates (RR = 1.15, 95% CI 1.06 to 1.25, P = 0.0009) and shorter resolution time for pulmonary rales (MD = −1.48, 95% CI −2.86 to −0.10, P = 0.04). In contrast, apparent benefits in the clinical effective rate (RR = 1.16, 95% CI 1.12 to 1.19, P < 0.00001), fever resolution time (MD = −1.31, 95% CI −2.07 to −0.55, P = 0.0007), C-reactive protein levels (standardized MD [SMD] = −0.99, 95% CI −1.55 to −0.43, P = 0.0005), and procalcitonin levels (SMD = −2.06, 95% CI −3.62 to −0.49, P = 0.01) were based on low or very low certainty evidence. These results should be interpreted cautiously and require confirmation in rigorously designed trials. There was no significant difference in the incidence of adverse events between groups (RR = 0.88, 95% CI 0.34 to 2.31, P = 0.80). The adverse events were minor and controllable, and no serious adverse events were reported.ConclusionShufeng Jiedu Capsule combined with biomedicine may offer advantages in treating respiratory diseases with wind-heat syndrome. The adverse events were minor and controllable, and no serious adverse events were reported. However, the reliability of these findings is limited by low evidence certainty arising from methodological weaknesses in the included trials. High-quality, multicenter RCTs with rigorous methodology are essential to confirm these results.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251017879, identifier CRD420251017879.